Peripapillary Retinal Nerve Fiber Layer Thickness and the Evolution of Cognitive Performance in an Elderly Population - Méndez-Gómez, Juan Luis; Rougier, Marie-Bénédicte; Tellouck, Laury; Korobelnik, Jean-François; Schweitzer, Cédric; Delyfer, Marie-Noëlle; Amieva, Hélène; Dartigues, Jean-François; Delcourt, Cécile; Helmer, Catherine (Frontiers in Neurology, 2017)
Retinal Nerve Fiber Layer thickness (RNFL) is reduced in Alzheimer's patients. However, whether it is associated with early evolution of cognitive function is unknown. Within 427 participants from the 3C-Alienor longitudinal population-based cohort we explored the relationship between peripapillary RNFL thicknesses and the evolution of cognitive performance. RNFL was assessed at baseline by Spectral-Domain Optical Coherence Tomography; cognitive performances were assessed at baseline and at 2years, with the Mini Mental State Examination, the Isaacs' set test and the Free and Cued Selective Reminding Test (FCSRT). Multivariate linear mixed models were performed. The RNFL was not associated with initial cognitive performance. Nevertheless, a thicker RNFL was significantly associated with a better cognitive evolution over time in the free delayed recall (p=0.0037) and free + cued delayed recall (p=0.0043) scores of the FCSRT, particularly in the temporal, supero-temporal and infero-temporal segments. No associations were found with other cognitive tests. The RNFL was associated with changes in scores that assess episodic memory. RNFL thickness could reflect a higher risk of developing cognitive impairment over time.